Limited adsorption selectivity of active carbon toward non-saccharide compounds in lignocellulose hydrolysate. (May 2016) - Wang, Zhaojiang; Zhuang, Jingshun; Wang, Xiaojun; Li, Zongquan; Fu, Yingjuan; Qin, Menghua
Graphical abstract: Highlights: Wood hydrolysate contains abundant hemicellulose-derived saccharides (HDS). Activated carbon (AC) was used to purify HDS from non-saccharide compounds (NSC). Competitive adsorption between HDS and NSC resulted in limited selectivity. Adsorption of oligomeric HDS was dominant while monomeric HDS was negligible. Abstract: Prehydrolysis of lignocellulose produces abundant hemicellulose-derived saccharides (HDS). To obtain pure HDS for application in food or pharmaceutical industries, the prehydrolysis liquor (PHL) must be refined to remove non-saccharide compounds (NSC) derived from lignin depolymerization and carbohydrate degradation. In this work, activated carbon (AC) adsorption was employed to purify HDS from NSC with emphasis on adsorption selectivity. The adsorption isotherms showed the priority of NSC to be absorbed over HDS at low AC level. However, increase of AC over 90% of NSC removal made adsorption non-selective due to competitive adsorption between NSC and HDS. Size exclusion chromatography showed that the adsorption of oligomeric HDS was dominant while monomeric HDS was inappreciable. The limited selectivity suggested that AC adsorption is infeasibility for HDS purification, but applicable as a pretreatment method.